Panton-Valentine leukocidin-positive methicillin-resistant Staphylococcus aureus correlates with disease severity in psoriasis: a case–control study. Issue 1 (2nd January 2019) - Masallat, Doaa T.; Eldars, Waleed; State, Ahmed F.; Moemen, Dalia
ABSTRACT: Psoriasis is a chronic inflammatory cutaneous disorder, which is prone to methicillin-resistant  Staphylococcus aureus  (MRSA) infection. We aimed to to investigate prevalence of MRSA skin colonization among psoriatic patients and if there is a relation between Panton-Valentin leukocidin  (PVL)  expression and disease severity. A case-control study was conducted on 90 patients with active psoriatic lesions and 90 healthy controls. Scales from psoriasis plaques and skin swabs from healthy control were collected. Identification of MRSA and antibiotic susceptibility patterns were performed using routine microbiological methods.  mecA  and  PVL  genes were detected using PCR assay and pulsed field gel electrophoresis (PFGE) was done for MRSA typing. Prevalence of MRSA among psoriatic patients was 23.3%. Significant difference was noticed in MRSA colonization between psoriasis and control groups. Five (23.8%) MRSA isolates from skin lesions were positive for  mecA  and  PVL  genes. Antibiotic resistance among  PVL  negative MRSA was higher, specially towards clindamycin. Patients harboring  PVL  positive isolates had significantly lower mean age and higher PSAI score than those with negative isolates. Fourteen PVL negative isolated MRSA from psoriasis patients were the same pulsotype. There was significant MRSA colonization in psoriasis group and presence of PVL may contribute to increased severity of this disease.